ESTIMATIVA DA REATIVIDADE DE FÊMEAS NELORE DURANTE MANEJOS REPRODUTIVOS - OLIVEIRA, Pedro Henrique Pereira; COSTA, Everton Garcia Areco Ximenez; BARBOSA, Taciara Aparecida Duarte; VILELA, Reíssa Alves; SANTOS, Tânia Mara Baptista (ANAIS DO ENIC, 2025)
-